Growth projections reveal local vulnerability of Mediterranean oaks with rising temperatures - Gea-Izquierdo, Guillermo; Fernández-de-Uña, Laura; Cañellas, Isabel (Forest Ecology and Management, 2013)
Growth projections using ecological models fitted to data collected along climatic gradients can help to understand how forests will respond to climate change. Stem growth of two Mediterranean oaks was predicted using nonlinear multiplicative models as a function of precipitation and minimum temperature of the hydrological year fitted to dendrochronological data. The growth of both species increased nonlinearly with accumulated precipitation before reaching an asymptote, but the species with a warmer niche (Q. ilex, an evergreen species) required lower levels of precipitation to achieve high relative growth. The species-specific relationship between growth and minimum temperature exhibited an optimum for the two species. Trees were negatively affected by high minimum temperatures whereas they responded negatively (Q. ilex) or neutrally (Q. pyrenaica, a deciduous species) to low temperatures along the climatic gradient analyzed. Growth would decrease rapidly when minimum temperatures rose above approximately 7 °C for Q. pyrenaica and 9 °C for Q. ilex. Most growth projections suggest a likely future decrease in productivity along the species range for Q. pyrenaica and particularly at species-specific warm, dry locations pointed to a future drastic reduction in productivity as a result of the increase in temperatures without a paired increase in precipitation forecasted by the different climate scenarios considered. In agreement with results from studies modeling future distribution of species this suggests that Q. pyrenaica could be threatened by climate change at the species local dry edge where, in addition, stands often present a lack of seed regeneration. More drought tolerant Q. ilex might profit from warming temperatures at cold northern locations but would also reduce productivity at warm, dry locations. Stem growth was successfully modeled using biologically meaningful species-specific responses to climate which provided key ecological information to understand the functional response of the two species. The models used have much potential to be applied with dendroecological data to study the response of forests to climate change.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Dendroecology; Forest decline; Global change; Nonlinear response; Quercus ilex; Quercus pyrenaica

INFLUENCIA DE LA ENCINA SOBRE LA PRODUCCIÓN Y LA COMPOSICIÓN DEL PASTO: CONSECUENCIAS SOBRE EL MANEJO SILVOPASTORAL - Gea Izquierdo, Guillermo; Cañellas, Isabel; Calama, Rafael; Sánchez Martín, Manuel Mario; Montero, Gregorio (IV Congreso Forestal Español, 2005)
El ecosistema de dehesa se extiende por más de 3x106 ha del O y SO peninsulares. Pese a su gran importancia económica y ecológica, su persistencia a corto plazo se encuentra amenazada, fundamentalmente por la falta de regeneración del arbolado y los cambios socioeconómicos. Por ello, resulta urgente desarrollar modelos de selvicultura que aseguren un desarrollo sostenible. El árbol es la base del sistema, influyendo, entre otros, sobre la producción animal, el suelo y la biodiversidad. Cualquier modelo selvícola a desarrollar deberá incluir los diversos factores del sistema, los cuales resultan diferentes a los de los ecosistemas forestales clásicos fundamentados en la producción de madera. En este estudio se realiza una aproximación a la influencia del arbolado adulto aislado sobre una comunidad herbácea de especies anuales. Para ello se ha estudiado en un año lluvioso la producción y composición del pasto en ocho distancias proporcionales al radio de copa según orientaciones NE y SO. La influencia del arbolado se deja sentir hasta el doble del radio de copa y de un modo diferencial según orientaciones, siendo más productivo el pasto situado al SO. La producción se incrementa significativamente bajo la copa en ambas orientaciones, aumentándose la proporción de gramíneas respecto del exterior
The following values have no corresponding Zotero field: periodical: IV Congreso Forestal Español pub-location: Zaragoza
Keywords: comunidad de anuales; Dehesa; modelos selvicultura; Quercus ilex

INFLUENCIA DE LA ENCINA SOBRE LA PRODUCCIÓN Y LA COMPOSICIÓN DEL PASTO: CONSECUENCIAS SOBRE EL MANEJO SILVOPASTORAL - Gea Izquierdo, Guillermo; Cañellas, Isabel; Calama, Rafael; Sánchez Martín, Manuel Mario; Montero, Gregorio (IV Congreso Forestal Español, 2005)
El ecosistema de dehesa se extiende por más de 3x106 ha del O y SO peninsulares. Pese a su gran importancia económica y ecológica, su persistencia a corto plazo se encuentra amenazada, fundamentalmente por la falta de regeneración del arbolado y los cambios socioeconómicos. Por ello, resulta urgente desarrollar modelos de selvicultura que aseguren un desarrollo sostenible. El árbol es la base del sistema, influyendo, entre otros, sobre la producción animal, el suelo y la biodiversidad. Cualquier modelo selvícola a desarrollar deberá incluir los diversos factores del sistema, los cuales resultan diferentes a los de los ecosistemas forestales clásicos fundamentados en la producción de madera. En este estudio se realiza una aproximación a la influencia del arbolado adulto aislado sobre una comunidad herbácea de especies anuales. Para ello se ha estudiado en un año lluvioso la producción y composición del pasto en ocho distancias proporcionales al radio de copa según orientaciones NE y SO. La influencia del arbolado se deja sentir hasta el doble del radio de copa y de un modo diferencial según orientaciones, siendo más productivo el pasto situado al SO. La producción se incrementa significativamente bajo la copa en ambas orientaciones, aumentándose la proporción de gramíneas respecto del exterior
Keywords: comunidad de anuales; Dehesa; modelos selvicultura; Quercus ilex

The influence of cork oak pruning on the yield and growth of cork - Cañellas, Isabel; Montero, Gregorio (Ann. For. Sci., 2002)
Bearing in mind the importance of pruning as a silvicultural treatment in cork oak (Quercus suber L.) open woodland of the dehesa type, an experiment was designed to assess the effect of pruning on cork yield. This work was carried out in two ways: synchronically, comparing pruned sites with others which were either unpruned or pruned at different times, and diachronically, comparing pruned and unpruned trees within the same site. The five test sites (with forty trees in the synchronic and eighty in the diachronic plots) were selected in south-west Spain. In all cases measurements of the cork production were made in kilos per square metre of surface stripped, total cork yield per tree, and the mean thickness of stripped cork. Analysis was carried out using a paired data comparison test. The effect of pruning on yearly cork growth was also analysed by examining the annual growth rings. In the five plots analysed there were no significant differences (95% confidence intervals) between pruned and unpruned trees in terms of kilos of cork produced per square metre of surface stripped, nor for total cork yield per tree. Neither were there significant differences in annual cork growth rings, even when the pruning was carried out during the cork-stripping period.
Keywords: cork growth; Cork Production; pruned biomass; pruning; Quercus suber